2020
DOI: 10.1051/0004-6361/201935872
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic detection of coronal plasma flows in loops undergoing thermal non-equilibrium cycles

Abstract: Context. Long-period intensity pulsations were recently detected in the EUV emission of coronal loops, and have been attributed to cycles of plasma evaporation and condensation driven by thermal non-equilibrium (TNE). Numerical simulations that reproduce this phenomenon also predict the formation of periodic flows of plasma at coronal temperatures along some of the pulsating loops. Aims. In this paper, we aim at detecting these predicted flows of coronal-temperature plasma in pulsating loops. Methods. To this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…The repeating cycle corresponds to periods of evaporation of chromospheric material that accumulates within the loop and periods of drainage of part of the material inside the loop in the form of precipitation that falls along the magnetic field lines. These condensation-evaporation cycles have their extreme ultraviolet (EUV) observational counterparts in the long period EUV pulsations, which have been described in recent studies (see Pelouze et al 2020;Auchère et al 2016Auchère et al , 2018Froment et al 2020).…”
Section: Introductionmentioning
confidence: 77%
“…The repeating cycle corresponds to periods of evaporation of chromospheric material that accumulates within the loop and periods of drainage of part of the material inside the loop in the form of precipitation that falls along the magnetic field lines. These condensation-evaporation cycles have their extreme ultraviolet (EUV) observational counterparts in the long period EUV pulsations, which have been described in recent studies (see Pelouze et al 2020;Auchère et al 2016Auchère et al , 2018Froment et al 2020).…”
Section: Introductionmentioning
confidence: 77%
“…Finally, flows develop during all TNE cycles, even if the plasma remains at coronal temperatures throughout the cycle and no condensation forms (Mikić et al 2013). The observation of such flows of plasma at coronal temperature was reported by Pelouze et al (2020).…”
Section: Introductionmentioning
confidence: 80%
“…On the other hand, observations with SST have revealed that these warm flows contain a large number of small cool chromospheric cores with densities on the order of 10 11 cm −3 or higher (see Figure 17, Antolin et al, 2015b;Froment et al, 2020), suggesting a tip-ofthe-iceberg clump distribution in which the bulk at smaller sizes may still be unresolved. Combined, these chromospheric and transition-region return flows to the solar surface show mass-flux values on the order of 1 -5 × 10 9 g s −1 (similar to prominences), suggesting that most of the material in the loop undergoes catastrophic cooling.…”
Section: Coronal Rainmentioning
confidence: 99%
“…Simulations have shown that the driver mechanism is very likely thermal non-equilibrium (Antiochos, DeVore, and Klimchuk, 1999;Froment et al, 2017Froment et al, , 2018. This scenario is presented by footpoint concentrated heating that is frequent enough (with a mean recurrent time less than the radiative cooling time), leading to cycles of heating and cooling (also known as evaporation and condensation cycles), with periodic EUV flows (Pelouze et al, 2020). Although globally the loop is in a non-equilibrium state, during the cooling stage thermal instability can set in to produce coronal rain (Antolin, 2020).…”
Section: Coronal Rainmentioning
confidence: 99%